Development of Traditional Sport Game Model “Bentengan” for Student’s Physical Fitness in Sports and Health Physical Education Learning (Case Study on Class IV MI Students of Maduran Lamongan District) - Moh. Syobil Birri; Agus Hariyanto; Abdul Rachman Syam Tuasikal (BIRCU, 2020)
The purpose of this development research is to improve physical fitness in the Physical Education learning process. The development of the traditional sports game model